The impacts of price insulation on world wheat markets during the 2022 food price crisis - Martin, Will; Minot, Nicholas (Wiley, 2022)
This paper begins with a survey of recent commodity price developments that highlights the magnitude of this price surge and identifies the rapid rise in wheat prices as a key element. The analysis in this paper focuses on the extent to which domestic markets are insulated from these changes and on the resulting impacts on world prices. An econometric analysis using error-correction models finds stable long-term relationships between world wheat prices and most domestic prices of wheat and wheat products, but with considerable variation across countries in the rate of price transmission. A case study of the price shocks during the COVID-19 pandemic and the Ukraine food price crisis finds that price insulation roughly doubled the overall increase in world wheat prices and raised their volatility both during periods of price increase and price decline.